DEVELOPMENT OF PERSONALITY VALUES IN A GLOBALIZED WORLD - Nevmerzhytska, Olena; Pahuta, Myroslav; Hamerska, Iryna; Voloshyn, Svitlana; Savchenko, Lyudmyla (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The modern world is extremely diverse. The processes of globalization in it contribute to the disappearance of borders: political, economic, religious, informational, etc. Personality is continuously facing the values of other cultures and other religions. By the way, he or she is not always able to properly evaluate and interpret them, what in its turn leads to the situation of conflict of values. The choice of necessary values becomes a complicated task and it definitely arises the need of pedagogical support of the process of values developing. Therefore, the situation described makes the problem of looking for the best ways of developing the values of the modern individual who lives in the world of values, where the chaos dominates, really topical, and that was the purpose of our research. Our poll conducted among teenagers and adolescents (n=120) proved an orientation towards their own and their family's problems, especially material ones. Instead, the decline in morality is an important social and personal problem for only a quarter of respondents, which makes the necessity to acquaint modern children and young people with higher values even more urgent. Educational institutions are challenged to assist students in the process of values choice in the complex axiological situations existing in the world, which is in the constant process of globalization. The search for ways of developing the values of the modern personality allowed us to identify the specific methods that contribute to the mastering of socially and personally significant values. These include text analysis (artistic, documentary, etc.), biographical methods, crystallization of values, problem solving, and more. These methods imply the active work of the pupil in the selection, mastering and appropriation of values, which will contribute to the formation of a highly moral personality with an active life position.